Critical race theory perspectives on the social studies : the profession, policies, and curriculum - Ladson-Billings, Gloria, 1947- (Emerald Publishing Limited : Information Age Publishing, 2003)
Fourteen American and Canadian academics contribute 13 chapters placing race at the center of an understanding of social studies practices in education. They consider ways the curriculum, profession, policies, and the current embrace of technology conform to a racial script which makes race invisible. By using critical race theory for their analyses, they prevent readers from turning to other factors to explain the ongoing inequities in schools and the society, and direct educators to recognize the gap between what is taught in the classroom and the real lives of the students attending schools.
Keywords: Social sciences -- Study and teaching.; Race -- Study and teaching.; Critical race theory.; Social Science -- Race & Ethnic Relations.; Racism and racial discrimination, Anti-racism.; Ethnic groups and multicultural studies.; elektronické knihy; electronic books